THE POLEMICS OF DELEGITIMIZING THE SUNNAH QAWLIYYAH FROM THE PERSPECTIVE OF MAHMUD ABU RAYYAH IN THE BOOK ADWA' 'ALA AL-SUNNAH AL-MUHAMMADÃŽYAH - arofik, slamet; Anam, Wahidul (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The existence of the Sunnah as an authoritative source after the Qur'an is accepted by the majority of Muslims both from Sunni, Shi'ah and other Islamic schools. Ironically, the authoritative Sunnah is viewed disproportionately by a group of Muslim outsiders and insiders. On the insider side, Mahmud Abu Rayah re-reads and delegitimizes the authority of Sunnah Qauliyyah as the second source of Islamic law by positioning the Qur'an as the first source, while Sunnah 'Amaliyyah is the second source. This paper aims to further examine Abu Rayah's delegitimization of Sunnah Qawliyyah and its polemics among Hadith scholars. This research is a Library Research with Qualitative approach and Historical and Text Study methods. The result of the research is that Mahmud Abu Rayah's perspective of Sunnah 'Amaliyyah has higher authority than Sunnah Qawliyyah. Sunnah Qawliyyah does not have the same authority as the Qur'an or Sunnah Amaliyyah. The implication is the rejection of the kutub hadith and kutub al-fiqh products of the kutub hadith.